Numerical study of the switching mechanism of a jet valve using the meshless method - Zhang, Jun (2021)
This study numerically investigates fluid dynamics of a jet flow at supersonic speed. The meshless method and the overlapping point cloud method are used to handle the moving boundary problems. The interaction between the jet flow and a moving ball-shaped plug is numerically solved, which has been rarely done in the published literature. The switching mechanism of a novel designed jet valve in an attitude and orbit control system (AOCS) is analyzed. It is found out that applied pressure to the control inlets of the jet valve must be high enough in order to successfully drive the plug to move and subsequently change the force direction acting on the jet valve. Then the switching mechanism of AOCS can be triggered. The initial fluid condition also plays a vital role and it significantly influences the response time of the switch. This study explores the underlying physics of the jet flow on its deflection, wall attachment, and interaction with the ball-shaped plug. It contributes to the optimization design of the jet valve in the AOCS with a fast and efficient response.